Building on institutional failures: The European Treaty on Stability, Coordination and Governance. Or: why the crisis in the Eurozone is so deep and persistent - Benjamin Coriat (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2014)
The paper is devoted to an analysis of the Treaty on Stability Coordination and Governance (TSCG), also known as the "Fiscal Compact" Treaty signed between the EU member states in 2012. We argue than the TSCG, instead of helping to "repair" the institutional failures on which the Euro and the Eurozone are built, strengthens them and further weakens the construction on which the European member states operate. In this sense, the Treaty explains why the crisis in Europe is so deep and persistent, and why the member states of the Eurozone are having such difficulty in returning to a path of balance and growth. After defining the "core" of the Treaty more precisely, by describing the nature and significance of the new rules it has introduced in more detail, we explain why these rules create supplementary obstacles in the road to recovery.
Keywords: H5; H6; G2; B5; 330; Fiscal Compact; ECB; public debt; European crisis